Smart Trolley by Using Bar Code/ Nur Izzati Md Asran - Md Asran, Nur Izzati (2020)
Izz Tech Sdn Bhd is introducing a new product to the customers which is the smart trolley by using bar code. Our company is targeting supply for smart trolley since it is people can estimate or calculate their daily budget grocer. Smart trolley can make people life easier when they entering the supermarket or hypermarket and also customer friendly which can help people from over budget. People either young or old can use this product safely. Other than that, our product can save people times like when they scanned all their items to the bar code scanner smart trolley can total up all the items and the user can do fast payment without waiting longer to do payment. We will sell our entire product to whole Malaysia to make it the product important to each supermarket. After for a next year, we will make sure our product will be sold worldwide with more efficient and more advanced of their technology. This way can make our company become the largest trolley manufacture. Our product will be always up date to make more efficient and maintain of the quality product. Then, our target market is retailer to all supermarket and hypermarket in Malaysia. We sold our product to certain group such as retailer at supermarket and hypermarket in Malaysia. This price of this product is not too low and not too high but it suitable price for the retailer to buy it. The target production of our company for second year is RM30000. The management teams of our company are divided into several sections and each of the section were led by experienced and professional employee to ensure our company’s product quality and efficiency.